Evidence of Agile Adoption in Software Organizations: An Empirical Survey - Papatheocharous, Efi; Andreou, Andreas S. (My University, 2013)
This paper aims at empirically investigating the levels of agile adoption by software development organizations in comparison with the type of practices followed, the business sectors and the countries of origin, as well as revealing the geographical organization and distribution of teams both within agile and traditional development environments. Through a dedicated survey conducted, the paper also discovers, analyzes and presents the business strategies, levels of expertise, benefits and concerns of agile adoption within the various participating organizations. The results obtained indicate that agile methods seem to offer opportunities for improved products in terms of quality and suggest a number of critical factors that affect the software process and the adoption of agile methods in general.
Keywords: Agile Software Development; Business Strategies; Empirical Survey; Level of Agile Adoption; Organizational Agile Expertise